Membranous glomerulonephritis in a patient with myelodysplastic syndrome-refractory cytopenia with multilineage dysplasia - Kwang Il Ko; Mi Jung Lee; Fa Mee Doh; Hyang Mo Koo; Chan Ho Kim; Dong Ho Shin; Hyung Jung Oh; Seung Hyeok Han; Shin-Wook Kang; Kyu Hun Choi; Tae-Hyun Yoo (The Korean Society of Nephrology, 2013)
A 74-year-old woman presented with edema in the lower extremities. Laboratory tests revealed anemia, thrombocytopenia, hypoalbuminemia, hypercholesterolemia, and nephrotic-range proteinuria. Myelodysplastic syndrome-refractory cytopenia with multilineage dysplasia (MDS-RCMD) was confirmed by bone marrow biopsy. Renal biopsy demonstrated membranous glomerulonephritis (MGN), stage I. Based on these clinicopathologic results, she was diagnosed as having MGN with MDS-RCMD. This is a rare case report of MGN in a parient with MDS-RCMD featuring nephrotic syndrome.